Combinations of Blue and Red LEDs Increase the Morphophysiological Performance and Furanocoumarin Production of Brosimum gaudichaudii Trécul in vitro - Costa, Érica Letícia Gomes; Farnese, Fernanda dos Santos; de Oliveira, Thales Caetano; Rosa, Márcio; Rodrigues, Arthur Almeida; Resende, Erika Crispim; Januario, Ana Helena; Silva, Fabiano Guimarães (Frontiers in Plant Science, 2021)
Brosimum gaudichaudii is a plant species with medicinal relevance due to its furanocoumarin accumulation. The accumulation of these compounds in the root promotes predatory extractivism, which threatens the conservation of the species. In addition, little is known about the conditions for culturing of this species in vitro. The present study aimed to investigate how the application of different spectra of LEDs (white, blue, red, and combinations of blue and red at 1:1 and 3:1 ratios) can impact the morphophysiological and biochemical characteristics of B. gaudichaudii under different in vitro conditions. To evaluate the production of furanocoumarins in its leaves, which are easy-to-collect perennial organs, we cultured nodal segments in 50-mL tubes with MS medium under 100 μmol m-2 s-1 light and a photoperiod of 16 hours for 50 days. We then submitted the seedlings biometric, anatomical, biochemical, and physiological evaluations. The different spectral qualities influenced several characteristics of the seedlings. Plants grown under red light showed greater stem elongation and larger and thinner leaves, strategies aimed at capturing a higher ratio of radiant energy. Exposure to the blue/red ratio of 1:1 induced increases in the concentration of the furanocoumarin psoralen, probably due to the diversion of carbon from primary metabolism, which resulted in lower growth. Cultivation under blue light or blue:red light at 3:1 triggered anatomical and physiological changes that led to higher production of secondary metabolites in the leaves, and at the 3:1 ratio, the seedlings also had a high growth rate. These results highlight the fundamental role of light in stimulating the production of secondary metabolites, which has important implications for the production of compounds of interest and indirect consequences for the conservation of B. gaudichaudii.